Societal Grand Challenges from a technological perspective: Methods and identification of classes of the International Patent Classification IPC - Rainer Frietsch; Peter Neuhäusler; Oliver Rothengatter; Koen Jonkers (Fraunhofer-Institut für System- und Innovationsforschung ISI, 2016)
[Introduction] The aim of this working paper is the provision of a list of IPC classes assigned to each of the technology-oriented Societal Grand Challenges (SGCs) of Horizon2020 and the description of the methods and workings steps that have led to this list. Patents are a vested right on the exclusive use of a certain technological solution. In consequence, patent data can only be collected for technology-driven or at least partially technology-affected areas. In terms of the Societal Grand Challenges, we see that six out of seven of them have at least in part a technology-affection, while one - namely "Europe in a changing world, inclusive, innovative and reflective societies" - can hardly be defined based on patent classes. We are fully aware of the fact that the Societal Grand Challenges have other, non-technical dimensions, which cannot be grasped on the basis of patents or patent statistics. Therefore, the aim of this paper is to provide a definition of the technological dimensions of the Societal Grand Challenges, while other dimensions will not be addressed. Next to definitions of patent classes for the six Grand Challenges, also definitions of the sub-fields of the Societal Grand Challenges will be provided. [...]
urn:nbn:de:0011-n-3895127; Additional information: This study was funded by the JRC-IPTS (Institute of Prospective Technology Studies) in the project with the title "Collection and analysis of private R&D investment and patent data in different sectors, thematic areas and societal challenges" (JRC/BRU/2014/J.6/0015/OC)
Keywords: 330